Safe-haven assets for U.S. equities during the 2020 COVID-19 bear market - Baek, Chung; Jackman, Thomas (Economics and Business Letters, 2021)
The recent stock market downturn is differentiated from the previous ones as it is due to an economic, rather than a financial occurrence (the COVID-19 Pandemic). The purpose of our study is to examine gold, bitcoin, and U.S. Treasury bonds as a safe haven during the COVID-19 bear market. Unlike many studies that support gold as a traditional safe haven for stocks, our study finds that bitcoin and Treasury bonds perform better as a safe haven than gold during the recent COVID-19 bear market.